Effect of Constrained Arm Posture on the Processing of Action Verbs - Yasuda, Masaaki; Stins, John F.; Higuchi, Takahiro (Frontiers in Neuroscience, 2017)
Evidence is increasing that brain areas that are responsible for action planning and execution are activated during the information processing of action-related verbs (e.g., pick or kick). To obtain further evidence, we conducted three experiments to see if constraining arm posture, which could disturb the motor planning and imagery for that arm, would lead to delayed judgment of verbs referring to arm actions. In all experiments, native Japanese speakers judged as quickly as possible whether the presented object and the verb would be compatible (e.g., ball–throw) or not (e.g., ball–pour). Constrained arm posture was introduced to the task by asking participants to keep both hands behind their back. Two types of verbs were used: manual action verbs (i.e., verbs referring to actions performed on an object by a human hand) and non-manual action verbs. In contrast to our hypothesis that constrained arm posture would affect only the information processing of manual action verbs, the results showed delayed processing of both manual action and non-manual action verbs when the arm posture was constrained. The effect of constrained arm posture was observed even when participants responded with their voice, suggesting that the delayed judgment was not simply due to the difficulty of responding with the hand (i.e., basic motor interference). We discussed why, contrary to our hypothesis, constrained arm posture resulted in delayed CRTs regardless of the “manipulability” as symbolized by the verbs.